The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1007/s42452-019-1480-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human serum on the stability and cytotoxicity of silver nanoparticles

Abstract: Silver nanoparticles are ubiquitous in today's commercial marketplace. Despite decades of research, there is still disagreement about the risk that silver nanoparticles pose to human and environmental health. There is often a lack of correlation between measured physical properties and the measured biological endpoints, making it difficult to establish trends, and discrepancies between different cell models have not been clearly accounted for. Here we have used human AB serum in cell culture media for the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…These interactions can cause particles to agglomerate, cause agglomerated particles to redisperse, or facilitate the dissolution of the particles by removing surface atoms. The rates of these processes are dependent on the composition of the serum (for example, which species it comes from) and its concentration [ 32 , 33 ]. Higher serum concentrations have a greater capacity to chelate free metal ions and may reduce cytotoxicity from dissolved ions.…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions can cause particles to agglomerate, cause agglomerated particles to redisperse, or facilitate the dissolution of the particles by removing surface atoms. The rates of these processes are dependent on the composition of the serum (for example, which species it comes from) and its concentration [ 32 , 33 ]. Higher serum concentrations have a greater capacity to chelate free metal ions and may reduce cytotoxicity from dissolved ions.…”
Section: Data and Resultsmentioning
confidence: 99%
“…The Ni-08 dispersion, the best dispersed sample in water, was able to maintain a submicron size for 3 days, although the high PDI values prevented a proper quantitative assessment. While we have previously used DLS measurements in cell culture medium to measure changes in silver nanoparticle dispersions, these heavily agglomerated NiO particles were not well-suited for this approach [ 32 , 33 ].…”
Section: Data and Resultsmentioning
confidence: 99%
“…We have previously noted that particles treated with human serum albumin are more stable than those coated with bovine serum albumin, the most abundant proteins in sera [26]. We have also shown that the size dependent stability of silver particles changes in media supplemented with human serum [27]. Here we have tested how commercial particles with different coatings behave in media with human proteins and biomolecules as opposed to those from fetal bovine serum, how the particles evolve over time and how that affects their uptake and cytotoxicty.…”
Section: Introductionmentioning
confidence: 84%
“…Neurotrophic factors have been identified as potentially therapeutic agents owing to their protective properties for photoreceptors in models of retinal and neuronal degeneration [ 1 , 2 , 3 ]. Neurotrophins (NTs), including brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT3), bind to their tropomyosin-related receptor kinase (TrkB and TrkC) and promote neuronal differentiation, survival, and plasticity [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%